الديون المتعثرة في المصارف الإسلامية وطرق معالجتها د ا رسة تطبيقية على مصرف النور ان نموذجا (Comprehensive Journal of Science, 2025)
This study aimed to identify the reality of non-performing debts in Libyan Islamic banks and methodsof treatment. The study used the descriptive approach through the use of content analysis methodfor a set of previous studies to achieve the objectives of the study. The study reached a number ofresults represented in the following: factors influencing the prioritization of debt treatment, challengesfacing non-performing debts, and the importance of continuous dialogue with customers andproviding flexible repayment plans. The study recommends enhancing communication withcustomers, developing flexible repayment policies, improving risk management, using technology,encouraging innovation, and strengthening cooperation with Sharia bodiesKeywords: Non-Performing Debts, Islamic Banks, Debt Treatment